Specification. Cold compressed hand forgings of aluminium-zinc-magnesium-copper-chromium alloy (solution treated and artificially aged to an overaged condition) (Zn 5.6, Mg 2.5, Cu 1.6, Cr 0.22). (28th May 1976) - British Standards Institution,
No abstract available